Molecular screening and dynamics simulation reveal potential phytocompounds in Swertia chirayita targeting the UspA1 protein of Moraxella catarrhalis for COPD therapy - Md. Moin Uddin; Md. Shydhur Rahman Chowdhury; Md. Arju Hossain; Asif Ahsan; Md. Tanvir Hossain; Abdul Barik; Md. Arif Hossen; Md. Faisal Amin; Rafsan Abir; Mohammad Shah Alam; Md Habibur Rahman; M. Nazmul Hoque (PLoS ONE, 2025)
Chronic obstructive pulmonary disease (COPD) is a global health burden, with Moraxella catarrhalis significantly contributing to acute exacerbations and increased healthcare challenges. This study aimed to identify potential drug candidates in Swertia chirayita, a traditional Himalayan medicinal plant, demonstrating efficacy against the ubiquitous surface protein A1 (UspA1) of M. catarrhalis through an in-silico computational approach. The three-dimensional structures of 46 phytocompounds of S. chirayita were retrieved from the IMPPAT 2.0 database. The structures underwent thorough analysis and screening, emphasizing key factors such as binding energy, molecular docking performance, drug-likeness, and toxicity prediction to assess their therapeutic potential. Considering the spectrometry, pharmacokinetic properties, docking results, drug likeliness, and toxicological effects, five phytocompounds such as beta-amyrin, calendol, episwertenol, kairatenol and swertanone were identified as the inhibitors of the UspA1 in M. catarrhalis. UspA1 demonstrated binding affinities of –9.1 kcal/mol for beta-amyrin, –8.9 kcal/mol for calendol, –9.4 kcal/mol for episwertenol, –9.6 kcal/mol for kairatenol, and –9.0 kcal/mol for swertanone. All of these affinities were stronger than that of the control drug ceftobiprole, which had a binding score of –6.6 kcal/mol. The toxicity analysis confirmed that all five compounds are safe potential therapeutic options, showing no toxicity or carcinogenicity. We also performed a 100 ns molecular dynamics simulation of the phytocompounds to analyze their stability and interactions as protein-ligand complexes. Among the five screened phytocompounds, beta-amyrin and episwertenol exhibited favorable characteristics, including stable root mean square deviation values, minimal root mean square fluctuations, and consistent radius of gyration values. Throughout the simulations, intermolecular interactions such as hydrogen bonds and hydrophobic contacts were maintained. Additionally, the compounds demonstrated strong affinity, as indicated by negative binding free energy values. Taken together, findings of this study strongly suggest that beta-amyrin and episwertenol have the potential to act as inhibitors against the UspA1 protein of M. catarrhalis, offering promising prospects for the treatment and management of COPD.